(untitled) (Journal of the College of Basic Education, 2026)
Abbasid poetry is one of the most prominent literary forms in Arab history, reflecting the social and political transformations witnessed during the Abbasid era. One of the topics that occupied a significant portion of poets’ attention was the elegies of Arab leaders. These poems embody feelings of loss and pain and highlight the values ​​these leaders represented in the eyes of their people. Elegies in Abbasid poetry are characterized by eloquence and emotional depth, with poets using a variety of techniques to convey feelings of grief while evoking the achievements and deeds of their leaders. The research aims to explore the images of elegy for Arab leaders in Abbasid poetry by analyzing selected poetic models, studying the social and political dimensions that shaped this type of elegy, and analyzing how poets used elegy for leaders as a means of expressing their national feelings. Such as the use of syntactic parallelism, similes, interrogation, vocatives and synonymous sentences, with the emergence of moral images that reflect eternity, such as generosity, patience and heroism, and rhetorical methods that reflect sadness and pride at the same time.